Exploiting phosphate-starved cells of scenedesmus SP for the treatment of raw sewage - Yewalkar-Kulkarni, Swati; Gera, Gayatri; Nene, Sanjay; Pandare, Kiran; Kulkarni, Bhaskar; Kamble, Sanjay (Indian Journal of Microbiology, 2017)
Phosphate depletion is one of the favorable ways to enhance the sewage water treatment with the algae, however, detailed information is essential with respect to internal phosphate concentration and physiology of the algae. The growth rate of the phosphate-starved Scenedesmus cells was reduced drastically after 48 h. Indicating cells entered in the stationary phase of the growth cycle. Fourier Transform Infrared analysis of phosphate-starved Scenedesmus cells showed the reduction in internal phosphate concentration and an increase in carbohydrate/phosphate and carbohydrate/lipid ratio. The phosphate-starved Scenedesmus cells, with an initial cell density of, 1 x 10(6) cells mL(-1) shows 87% phosphate and 100 % nitrogen removal in 24 h. The normal Scenedesmus cells need approximately 48 h to trim down the nutrients from wastewater up to this extent. Other microalgae, Ankistrodesmus, growth pattern was not affected due to phosphate starvation. The cells of Ankistrodesmus was able to reduce 71% phosphate and 73% nitrogen within 24 h, with an initial cell density of, 1 x 10(6) cells mL(-1).
Keywords: Ankistrodesmus; Fourier Transform Infrared; Phosphate starvation; Scenedesmus; Sewage treatment